Sign and Symptom and Ability to Control Violent Behaviour with Music Therapy and Rational Emotive Cognitive Behaviour Therapy - Heri Setiawan; Budi Anna Keliat; Ice Yulia Wardani (Universitas Airlangga, 2015)
Introduction: Prevalence of violence is highly occur in mental disorders clients at psychiatric hospitals. The impact is injure to others. This research aims to examine the effectiveness of music therapy and RECBT to sign and symptom and ability to control violent behaviour.Methods: Quasi-experimental research design with a sample of 64 respondents.Result: The study found a decrease symptoms of violent behaviour, ability to control violent behavior include relaxation, change negative thingking, irational belief, and negative behavior have increased significantly than the clients that did not receiving therapy.Discussion: Music therapy and RECBT is recommended as a therapeutic nursing at the client’s violent behaviour.Discharge Planning Increase Therapy Obedient of Patients